Reforestation could bring native mammal species back in the tropical highlands - Wahdaniyah, Siti; Khalidah, Ku Noor; Sabar, Nabilah Hamidah; Kamarudin, Norizah; Sanusi, Ruzana; Razi, Norhisham Ahmad; Lechner, Alex M.; Azhar, Badrul (Springer, 2023)
The rapid conversion of highland forests into agricultural areas has caused deforestation in Peninsular Malaysia. Since 2017, in the Cameron Highlands, the Forestry Department of Peninsular Malaysia has reforested degraded highland areas by planting native tree species. To date, little is known about the effect of highland reforestation on wild mammals in the region. This study aimed to examine the relationship between mammal detections and habitat variables in the reforested areas that previously had been coverted into intensively managed vegetable farms (for at least 10 years), using camera trapping over four forest reserves. Seven wild mammal species were detected across the study area, including conservation priority species such as the Sumatran serow (Capricornis sumatrensis), the otter civet (Cynogale bennettii), and the Asian golden cat (Catopuma temminckii). The wild boar (Sus scrofa) had the highest detection and leopard cat (Prionailurus bengalensis) was the most common carnivorous species at almost all of the study sites. Eight predictor variables determined mammal detection numbers in the highland reforestation areas. Mammal detections increased with elevation, sapling abundance, and number of trees with a DBH above 5 cm. While, detection numbers decreased with the number of fallen trees, palm abundance, and undergrowth coverage. Mammal detections varied with forest reserves and sampling months. Continuous monitoring is vital to understand long term trends in reforestation on wild mammal communities in highland areas, however, the outcome of our study is very promising and suggests reforestation could help reverse defaunation of highland forests in Peninsular Malaysia.